Dynamics of Women's Leadership Thought from the Perspective of Amina Wadud and Zainab Al-Ghazali - Eka Nurhidayat; Muhammad Arifin; Inayatillah; Abdul Manan; Sa’i (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
This study investigates the dynamics of women’s leadership thought in Islam by examining the perspectives of Amina Wadud and Zainab al-Ghazali. The background of this research arises from ongoing debates regarding the legitimacy of women’s leadership, which are shaped not only by interpretations of religious texts but also by differences in epistemological approaches. The study aims to analyze how these distinct frameworks influence the conceptualization of leadership for women in Islamic contexts. A qualitative approach was employed, using library research and a descriptive-comparative method to examine primary sources from both figures, supplemented by supporting literature in gender studies and contemporary Islamic scholarship. The findings indicate that Amina Wadud adopts a contextual hermeneutic approach, emphasizing justice, equality, and social relevance, thereby broadening opportunities for women’s leadership. In contrast, Zainab al-Ghazali employs a normative-textual approach that reflects classical traditions and imposes certain limitations on women’s roles in leadership. These differences demonstrate that epistemological frameworks significantly shape interpretations of women’s leadership in Islam. Despite these divergences, both scholars recognize the importance of women’s participation in the public sphere. The study concludes that a dialogical and integrative approach, combining contextual and normative perspectives, offers a viable pathway for formulating a concept of women’s leadership that is both adaptive and relevant to the needs of contemporary Muslim society.